Nurse-patient interaction in view of appraisal language - Križan, Agata (Scripta manent (Ljubljana), 2021)
Since the quality of communication between nurses and patients has a significant impact on their relationship and ultimately on patients’ well-being, the nurses’ use of language is undoubtedly critical. Due to increased mobility and migration in today’s globalised world, there is a growing need for trainee nurses to learn English and, particularly, for nurses to use English effectively in their communication with both native and non-native English-speaking patients. The paper explores the occurrence of appraisal, which is the language of evaluation, in nurses’ propositions in sample nurse-patient interactions in English by applying the appraisal model (Martin & White, 2005) with the aim of establishing if and how nurses’ propositions employ appraisals that help build a good rapport with patients, and thus effective interaction. Our data show that nurses’ propositions in these interactions with patients frequently employ language that explicitly and implicitly evaluates nurses’ behaviour and approaches towards their patients positively, which is significant due to the educational purposes of these sample interactions. It is hoped that the findings here will help improve trainee nurses’ communication with patients, as well as increase their awareness of appraisal as a potential linguistic means of a good rapport building.
Keywords: angleščina za posebne namene; appraisals; bodoče medicinske sestre; ESP; future nurses; jezik vrednotenja; komunikacija; nurse-patient communication; odnosi; support